Immediate Weight-Bearing after Ankle Fracture Fixation - Reza Firoozabadi; Emily Harnden; James C. Krieg (Advances in Orthopedics)
We believe that a certain subset of surgical ankle fracture patients can be made weight-bearing as tolerated immediately following surgery. Immediate weight-bearing as tolerated (IWBAT) allows patients to return to ambulation and activities of daily living faster and may facilitate rehabilitation. A prospectively gathered orthopaedic trauma database at a Level 1 trauma center was reviewed retrospectively to identify patients who had ORIF after unstable ankle injuries treated by the senior author. Patients were excluded if they were not IWBAT based on specific criteria or if they did meet followup requirement. Only 1/26 patients was noted to have loss of fixation. This was found at the 6-week followup and was attributed to a missed syndesmotic injury. At 2-week followup, 2 patients had peri-incisional erythema that resolved with a short course of oral antibiotics. At 6-week followup, 20 patients were wearing normal shoes and 6 patients continued to wear the CAM Boot for comfort. To conclude, IWBAT in a certain subset of patients with stable osteosynthesis following an ankle fracture could potentially be a safe alternative to a period of protected weight-bearing.